Perspektif Gender Dalam Novel Bekisar Merah Karya Ahmad Tohari Tinjauan : Sastra Feminis Dan Implementasinya Pada Pembelajaran Sastra Di Sma - Setiyawan, Dwi; , Dr. Nafron Hasyim (2017)
This study have three purpose 1) the structure novel Bekisar Merah by Ahmad Tohari 2) the nature of gender equality in the work Bekisar Merah novel by Ahmad Tohari, and 3) the implementation of novel research results Bekisar Merah by Ahmad Tohari work in teaching literature in senior highschool. The data in this study in the form of words, sentences, phrases, and the discourse that contain elements of gender issues in the novel Bekisar Merah. Mechanical footage used is purposive sampling while collecting data usingbook, correct reading and noted. Test the validity of the data that is applied is triangulation. Data were analyzed using reading techniques semiotic models consisting of heuristic and hermeneutic reading. 1) Bekisar Merah novel structure that is based on the theory of fiction Robert Stanton theme of women in the struggle for gender equality with men. The fact the novel is divided into three, namely character and characterization, setting, and plot. 2) As a form of gender equality, namely (a) women as equals to men, (b) the rights and obligations similarities between men with women, and (c) against violence against women. 3) The results are implemented in the learning scenarios with KD 7.2 Analysis the elemen intrinsic or exstrinsic of novel (originalor translation), which is scheduled in two meetings. The first meeting, focused on the delivery of content on the novel, novel intrinsic elements, aspects of gender inequality and ordinances argue with courtesy, good, and true as well as the provision of duty of teachers. The second meeting was followed by a presentation and discussion of the results of the tasks that have been worked on the student. Keywords: novel Bekisar Merah, education values, gender equality, implementation education in senior high School